Marketing Mix Analysis on Brand Image and its Impact on Running Shoe Purchase Decisions in E-Commerce - Muhammad Ishar; Nunung Ayu Sofiati; Mochammad Mukti Ali; Dadan Abdul Azis; Gurawan Dayona; Riyadi Nur Sumawidjaya; Ade Salman Alfarisi; Anggono Raras Tirto Sakti (International Journal of Advanced Multidisciplinary, 2026)
This study aims to analyze the influence of the Marketing Mix on Brand Image and its impact on Purchasing Decisions for running shoes on e-commerce platforms. The rapid development of digital commerce has changed consumer behavior in selecting and purchasing products, making marketing strategy, brand perception, and online purchasing decisions crucial aspects for business competitiveness. This research adopts a quantitative approach with descriptive and verificative methods to examine the relationships among the variables of Marketing Mix, Brand Image, and Purchasing Decisions. The results indicate that the implementation of the Marketing Mix, covering Product, Price, Place, and Promotion, is in the good category with an average score of 3.66, reflecting effective marketing strategy execution. Brand Image, measured through Reputation, Recognition, Affinity, and Loyalty, is also in the good category with an average score of 3.57, indicating positive consumer perception of the brand. Similarly, Purchasing Decisions, including product selection, e-commerce selection, and repeat purchases, are in the good category with an average score of 3.40. Furthermore, statistical analysis reveals that the Marketing Mix has a positive and significant effect on Brand Image and Purchasing Decisions, while Brand Image also significantly influences Purchasing Decisions. Additionally, the Marketing Mix simultaneously exerts a significant effect on both Brand Image and Purchasing Decisions, demonstrating the strategic role of integrated marketing strategies in enhancing consumer behavior in the e-commerce context.